Comparison of Immunized and Non-Immunized Women Against the Rubella Virus in Relation to Toxoplasmosis in Kirkuk, Iraq - Ali, Ola Salih (American Journal of Bioscience and Clinical Integrity, 2026)
Rubella and toxoplasmosis are significant teratogenic infections that may cause serious complications in pregnant women, particularly in regions with limited vaccination coverage and insufficient public health awareness. This study aimed to compare the incidence of rubella virus infection and toxoplasmosis among vaccinated and non-vaccinated women in Kirkuk, Iraq, through the assessment of their immunological status. A cross-sectional study was conducted involving 160 women, aged 15-45 years. Blood samples were collected from all participants, and enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of IgM and IgG antibodies against Toxoplasma gondii and rubella virus. Participants were classified according to vaccination status and pregnancy condition. The effect of immunization was confirmed by the significantly higher prevalence of Rubella IgG seropositivity among vaccinated women compared with unvaccinated women (p < 0.00001). In contrast, Toxoplasma IgM positivity was higher in the unvaccinated group (23.6 %), indicating recent exposure to infection. No significant correlation was observed between toxoplasmosis and rubella vaccination status. The findings highlight the importance of dual screening programs for pregnant women and emphasize the need of strengthen vaccination strategies. Public health interventions should address both viral and parasitic infections to reduce the risk of congenital complications.